2012
DOI: 10.1111/j.1365-3059.2012.02673.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of guttation in the secondary spread of Clavibacter michiganensis subsp. michiganensis in tomato greenhouses

Abstract: Bacterial canker, caused by Clavibacter michiganensis subsp. michiganensis (Cmm), can spread in commercial tomato greenhouses causing epidemics. Results of greenhouse experiments with Cmm-contaminated tools demonstrated disease spread for only a limited distance (<4 plants) from infected plants. However, touching symptomless infected plants bearing guttation droplets prior to touching nearby plants spread the pathogen over longer distances within rows (>22 plants). The pathogen was exuded in large numbers in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 31 publications
(45 reference statements)
2
25
0
1
Order By: Relevance
“…These procedures facilitate pathogen invasion of the vascular tissues of target plants through the newly opened wounds, leading to systemic infection (Gleason et al, 1991;Kawaguchi et al, 2010). Moreover, it has recently been shown that touching symptomless infected plants bearing guttation droplets prior to touching nearby plants transfers the pathogen, which is exuded in the guttation fluid, within rows (Sharabani et al, 2012). The results presented here demonstrate the importance of defining the window of vulnerability for effective disease control.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These procedures facilitate pathogen invasion of the vascular tissues of target plants through the newly opened wounds, leading to systemic infection (Gleason et al, 1991;Kawaguchi et al, 2010). Moreover, it has recently been shown that touching symptomless infected plants bearing guttation droplets prior to touching nearby plants transfers the pathogen, which is exuded in the guttation fluid, within rows (Sharabani et al, 2012). The results presented here demonstrate the importance of defining the window of vulnerability for effective disease control.…”
Section: Discussionmentioning
confidence: 76%
“…Samples were weighed and macerated in sterile distilled water. Serial tenfold dilutions in distilled water were prepared and 100 lL of each dilution was plated on three mCNS plates (Sharabani et al, 2012). Plates were incubated at 28°C and the resulting colonies were counted 5 days later.…”
Section: Determination Of Cmm Population Sizementioning
confidence: 99%
“…The disease progresses rapidly between 24 and 32 °C (Strider, 1969). In addition, the disease develops more rapidly in soil at a water-holding capacity (WHC) of 80 % (which is optimal for growth of tomatoes) than at a WHC of 40 % or 100 %, at a low light intensity, in young plants (Sharabani et al, 2013), under high nutrient conditions, in sandy rather than organic soils (Strider, 1969) and at high rather than low relative humidity (Xu et al, 2012). When leaves of tomato plants were spray inoculated, distinct symptoms presented at a high humidity of 87-97 %, slight symptoms at 75-85 %, and no symptoms at 50-70 % (Basu, 1966).…”
Section: Suitability Of Environmentmentioning
confidence: 99%
“…Systemic infection with high populations, >10 8 CFU/g, lead to characteristic wilting, stem canker, and vascular discoloration (Bryan 1930;Gartemann et al 2003). Additionally, the pathogen can ooze from cankers and hydathodes (in guttation droplets), and in combination with rain and wind or through cultural practices, spread to distal leaves, fruit, and surrounding plants (Bryan 1930;Sharabani et al 2013).…”
Section: Introductionmentioning
confidence: 98%